INTEGRATIVE ESTIMATE OF AIR TRAFFIC CONTROL STUDENTS ATTITUDE TO THE DANGER OF LIGHT LEVEL NORMS VIOLATION - Рева, О. М.; Борсук, С. П.; Мірзоєв, Б. М. (Science-based technologies, 2016)
Taking into account influence of human factor on flight safety; multiplicative approach to determination of integral estimate of air traffic controllers attitude to aircrafts separation norms violation; was developed firstly in area of air traffic controllers professional activity researches. Harrington desirability function adapted during researches allows to generalize indexes of main decision taking dominants; desirability levels; and fuzzy estimates for flight separation norms violation risks according to ICAO scale. Inexpedience of using desirability coefficients to determine air traffic controllers attitude to single flight separation norm is proved. Corresponding index varies in j(S)=0;69–0;74 limits; and greater violations are allowed for bigger norms by air traffic control students. With help of priority rearrangement method weight coefficients of these norms were defined that allowed to find integral index of attitude to all flight level norms violation which is equal to j(S)=0;94.